2019
DOI: 10.1111/cup.13566
|View full text |Cite
|
Sign up to set email alerts
|

A pediatric case of pigmented epithelioid melanocytoma with chromosomal copy number alterations in 15q and 17q and a novel NTRK3‐SCAPER gene fusion

Abstract: Pigmented epithelioid melanocytoma (PEM) represents a group of rare, heavily pigmented melanocytic tumors encompassing lesions previously designated as "animal-type melanomas" and "epithelioid blue nevi." Despite the association of multiple such tumors in the setting of Carney complex, most cases of PEM occur spontaneously as solitary neoplasms in otherwise healthy patients. PEM may arise in both children and adults, and has a known propensity to spread to the regional lymph nodes.Despite this latter finding, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 15 publications
2
8
0
Order By: Relevance
“…Recent studies have reported that the tyrosine kinase domain of TrkC and ETV6-NTRK3 interacts with the SH2 domain of the Src and PTB domain of IRS-1. Ligand-independent PTK activation of ETV6-NTRK3 and TrkC in breast and colon cancer leads to constitutive activation of the Ras-MAP kinase (MAPK) mitogenic pathway and the phosphatidylinositol 3-kinase (PI3K)-AKT pathway, as well as upregulation of cyclin D1 mediating cell survival [111,113], In addition, its activation by TrkC and ETV6-NTRK3 is mediated via activation of c-Src by using complex formation [130,131]. IRS-1 functions as an adapter protein, linking ETV6-NTRK3 and TrkC for constitutive activation of downstream signals.…”
Section: The Biological Function Of Trkc In Cancermentioning
confidence: 99%
“…Recent studies have reported that the tyrosine kinase domain of TrkC and ETV6-NTRK3 interacts with the SH2 domain of the Src and PTB domain of IRS-1. Ligand-independent PTK activation of ETV6-NTRK3 and TrkC in breast and colon cancer leads to constitutive activation of the Ras-MAP kinase (MAPK) mitogenic pathway and the phosphatidylinositol 3-kinase (PI3K)-AKT pathway, as well as upregulation of cyclin D1 mediating cell survival [111,113], In addition, its activation by TrkC and ETV6-NTRK3 is mediated via activation of c-Src by using complex formation [130,131]. IRS-1 functions as an adapter protein, linking ETV6-NTRK3 and TrkC for constitutive activation of downstream signals.…”
Section: The Biological Function Of Trkc In Cancermentioning
confidence: 99%
“…Other, less commonly found, fusions in their study were TPR – NTRK1 (6%, 1/16), ALK (6%, 1/16), and MYO5A – NTRK3 (6%, 1/16) 55 . More recently, rare cases of PEM with NTRK3 – SCAPER 56 or HTT – PKN1 57 fusion have also been reported. Only limited data exist on copy number changes in PEMs; Cohen et al 54 .…”
Section: Melanocytic Lesions With Bn‐like (Dendritic) Morphologymentioning
confidence: 81%
“…failed to detect significant copy number aberrations in their series of 13 cases. More recently, Friedman et al 56 . reported a case with copy number alterations involving chromosomes 15q and 17q.…”
Section: Melanocytic Lesions With Bn‐like (Dendritic) Morphologymentioning
confidence: 99%
“…5). Given the discrepant “benign” gene expression score, peculiar cytology, and deceptively low-grade nuclear pleomorphism, additional analysis via chromosomal microarray (via previously described methods 6 ) was pursued. Multiple deleterious segmental gains and losses were detected, which was more indicative of a malignant phenotype and consistent with our impression of a malignant lesion based on the overall histomorphologic and immunophenotypic features.…”
Section: Report Of a Casementioning
confidence: 99%